Perancangan Alih Fungsi Kontainer Menjadi Modul Ruang Komersial ‘Tailor & Modiste’ - Yulianto Kurniawan; Yusita Kusumarini; Meirina Kuncahyowati (Intra, 2019)
Re-functioning container to become module system commercial space started with an offer from Pondok Kasih Foundation Surabaya to design a container to become a working space. From that offer, it has a potential to become a business concept, and that is module system container for multipurpose space. The container is designed to facilitate small businesses, in this case the business is a tailor. It has an easy to fit concept and more oriented to the tailor. Because 90% of the room are used by the tailor, this easy to fit concept are used to make tailor activity more efficient and easy. Helped with few custom designed furniture to help tailor on their work. This module is designed to help new small business so they can have a better business opportunities, a space to start their business, and also contribute to reduce unused container.